METODE AKUNTANSI PADA PERUSAHAAN-PERUSAHAAN YANG TERGABUNG DALAM KELOMPOK LQ45 DI BURSA EFEK INDONESIA: SUATU KAJIAN - Riko Mappedeceng (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2016)
This research intends to know the most accounting methods that used by companies to take a decision in account receivable, inventory and fixed asset. Moreover it can be used as a consideration to choose an accounting method for the companies’ bad debt, initial cost of inventory and depreciation of fixed asset. This research proved that the most method used in account receivable is allowance method, for inventory is the lower cost or market method, and for fixed asset is the straight line method.Key words : Accounting Method